Salinas De Los Nueve Cerros, Guatemala: A Major Economic Center in the Southern Maya Lowlands. Issue 2 (June 2015) - Woodfill, Brent K.S.; Dillon, Brian Dervin; Wolf, Marc; Avendaño, Carlos; Canter, Ronald
Abstract : Salinas de los Nueve Cerros is a precolumbian Maya city located at the base of the highlands in the lowlands of west-central Guatemala. It is the only Classic-period center in the southern Maya Lowlands that based its economy on the production of an important raw material for export: salt. Because of its economic role and its location along a major trade route, Salinas de los Nueve Cerros had a particularly long history of occupation. The site has evidence of a large sedentary population starting during the Middle Preclassic (by ca. 800 B.C.) that continued several hundred years beyond the Classic collapse, before finally being abandoned ca. A.D. 1200. The salt source was located in the center of the city. This presents a rare opportunity to test the degree of elite control over the production of a non-elite resource. Production during the Classic period does appear to have been tightly controlled by elites, as evinced by the presence of multiple administrative structures and elite tombs throughout the salt-working zone, located less than 100 mfrom the site epicenter.